2019
DOI: 10.1038/s41467-019-11560-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary modification of AGS protein contributes to formation of micromeres in sea urchins

Abstract: Evolution is proposed to result, in part, from acquisition of new developmental programs. One such example is the appearance of the micromeres in a sea urchin that form by an asymmetric cell division at the 4 th embryonic cleavage and function as a major signaling center in the embryo. Micromeres are not present in other echinoderms and thus are  considered as a derived feature, yet its acquisition mechanism is unknown. Here, we report that the polarity factor AGS and its associated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…In addition to the aforementioned mechanisms, the enrichment of sea urchin Vasa is coupled to asymmetric cell division that results from the recruitment of AGS, a polarity factor, to the vegetal cortex (Poon et al, 2019). It has been postulated that acquisition of an additional GoLoco motif in the C‐terminus of the sea urchin AGS is important for the vegetal accumulation of the AGS‐Vasa complex (Poon et al, 2019). Using the sea urchin AGS sequence as a query, we identified a partial ags transcript in our P. flava transcriptome data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned mechanisms, the enrichment of sea urchin Vasa is coupled to asymmetric cell division that results from the recruitment of AGS, a polarity factor, to the vegetal cortex (Poon et al, 2019). It has been postulated that acquisition of an additional GoLoco motif in the C‐terminus of the sea urchin AGS is important for the vegetal accumulation of the AGS‐Vasa complex (Poon et al, 2019). Using the sea urchin AGS sequence as a query, we identified a partial ags transcript in our P. flava transcriptome data.…”
Section: Discussionmentioning
confidence: 99%
“…The exact location of each antigen sequence within SpRb1 is indicated in Table S3. Immunoblot was performed as described previously . Briefly, 2 μl each of embryonic lysate made from Day 2 embryos was run on a 10% polyacrylamide gel (Lonza, Rockland, ME) and transferred to nitrocellulose membranes for immunoblotting with rabbit polyclonal SpRb1 antibody #1–3 each or with mouse monoclonal β‐actin antibody (Cell Signaling Technology, #3700) at 1:2000 followed by HRP‐conjugated anti‐rabbit (Cell Signaling Technology, #7047) or anti‐mouse secondary antibody (Cell Signaling Technology, #7076), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot was performed as described previously. 33 Briefly, 2 μl each of embryonic lysate made from Day 2 embryos was run on a 10% polyacrylamide gel (Lonza, Rockland, ME) and transferred to nitrocellulose membranes for immunoblotting with rabbit polyclonal SpRb1 antibody #1-3 each or with mouse monoclonal β-actin antibody (Cell Signaling Technology, #3700) at 1:2000 followed by HRP-conjugated anti-rabbit (Cell Signaling Technology, #7047) or anti-mouse secondary antibody (Cell Signaling Technology, #7076), respectively. The reacted proteins were detected by incubation in a chemiluminescence solution (1.25 mM luminol, 68 μM coumeric acid, 0.0093% hydrogen peroxide and 0.1 M Tris pH 8.6) for 1-10 minutes, exposed to film and developed.…”
Section: Sprb1 Antibody Production and Immunoblottingmentioning
confidence: 99%
“…The polarity factor AGS is both necessary and sufficient to establish this physical and molecular ACD. Sea urchin AGS contains three GoLoco motifs, whereas sea star AGS lacks GoLoco motif #1, and it was recently shown that expressing sea urchin AGS in sea star embryos is sufficient to induce physical ACDs (Poon et al, 2019). It has also been shown that the core cortical force-generating machinery responsible for such cortical pulling forces is evolutionarily conserved and contains the Dynein-Dynactin complex, NuMA (Lin5 in C. elegans; Mud in Drosophila) and the Gαi complex (GOA-1, GPA-16 in C. elegans;…”
Section: Spindle and Cell Size Asymmetrymentioning
confidence: 99%